2002
DOI: 10.1007/s11661-002-0049-x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of microstructure and grain-boundary evolution during ECA pressing of pure aluminum

Abstract: High-purity aluminum (99.99 pet) was processed by equal-channel angular pressing (ECAP) at room temperature through a die with a 90 deg angle between the die channels. Samples were examined by transmission electron microscopy (TEM) and orientation imaging microscopy (OIM) methods after one, four, and 12 passes through the die. Repetitively pressed samples were rotated by 90 deg in the same sense between successive pressing operations (route Be). After one pressing, TEM showed a subgrain structure which was elo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
128
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(159 citation statements)
references
References 38 publications
28
128
2
1
Order By: Relevance
“…There is also evidence in all three distributions for the presence of two peaks at the higher angles, with these peaks lying in the vicinity of misorientation angles of ∼35 • and ∼60 • , respectively. A similar effect was reported in experiments on pure Al processed by ECAP [33] and the second peak corresponds to the twin misorientation.…”
Section: The Grain Boundary Misorientation Distributionssupporting
confidence: 85%
“…There is also evidence in all three distributions for the presence of two peaks at the higher angles, with these peaks lying in the vicinity of misorientation angles of ∼35 • and ∼60 • , respectively. A similar effect was reported in experiments on pure Al processed by ECAP [33] and the second peak corresponds to the twin misorientation.…”
Section: The Grain Boundary Misorientation Distributionssupporting
confidence: 85%
“…For instance 7 it was shown that grain refinement mainly takes place after the first pass, saturation being reached by the sixth and eighth passes. This confirms previous findings by Langdon 8 which were obtained on Al samples. It is important to point out that this effect of the first pass on grain size appears to be a fundamental occurrence, not confined to this or that material.…”
Section: Introductionsupporting
confidence: 93%
“…Full details of the materials and processes of this work have been given previously [12,13]. Briefly, the pure aluminum material (99.99%) was swaged to a rod 10 mm in diameter and 60 mm in length for pressing in the 90 • die.…”
Section: Methodsmentioning
confidence: 99%
“…The symmetry of an ECAP billet is monoclinic, and so the senses of the coordinate axes in the flow plane were carefully ascertained. Transmission electron microscopy (TEM) foil preparation has been described previously [13]. Fig.…”
Section: Methodsmentioning
confidence: 99%